Fingerprint Template Protection using Encrypted Fuzzy Vault - Dhillon, Shamsher Singh (My University, 2017)
Fingerprints are by far the most popular biometric features in authentication systems because of their capability to satisfy implementation specifications. Throughout the last two decades, exploration in fingerprint-based authentication systems has observed incredible development. Lately, fingerprints are already employed to authenticate individuals remotely enabling them to access a system. For example, smart phones now have an embedded fingerprint scanner to authenticate a user. Although fingerprints are now being used extensively to protect information as well as for the process of authentication, even the biometric systems are vulnerable to attacks. Some of these attacks may be targeted to the system while other may be carried out with the intention of stealing biometric information of users of the biometric systems. Due to the value of biometric information in recent times, it must be ensured that the biometric information of the users stored in the system is secure and even during a case of a break-in, the users and their information is protected. There has been some research in this area and certain promising methods have been proposed to secure the biometric information in a biometric system. In this thesis, we present such a technique that can be potentially used to protect the biometric information of the users.
Keywords: Fuzzy Vault; Finger Print; Encryption